2002
DOI: 10.1002/cncr.11054
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the incidence of testicular germ cell tumors in the United States

Abstract: BACKGROUND Recent reports have suggested that the increasing rates of testicular germ cell tumors in some populations have begun to plateau. This study was conducted to examine whether rates among white men in the United States have begun to stabilize and whether rates among black men in the United States have remained low. METHODS Testicular germ cell tumor incidence data from in the Surveillance, Epidemiology, and End Results Program were analyzed for the years 1973–1998. Trends were examined separately for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
204
4
8

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 299 publications
(233 citation statements)
references
References 32 publications
16
204
4
8
Order By: Relevance
“…Evidence that race plays a role in this disease is provided by the fact that the incidence is over five times greater in Caucasian Americans compared to African Americans. 8 The only nonwhite population with a relatively high incidence of TGCT is the Maoris of New Zealand. 9 Interestingly, the incidence of TGCT in many countries has increased significantly during the last century.…”
Section: Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…Evidence that race plays a role in this disease is provided by the fact that the incidence is over five times greater in Caucasian Americans compared to African Americans. 8 The only nonwhite population with a relatively high incidence of TGCT is the Maoris of New Zealand. 9 Interestingly, the incidence of TGCT in many countries has increased significantly during the last century.…”
Section: Incidencementioning
confidence: 99%
“…9 Interestingly, the incidence of TGCT in many countries has increased significantly during the last century. 8,[10][11][12] Based on SEER data, McGlynn and collaborators reported an overall rise of 44% in the incidence in the United States from 1973 to 1998, from 3.35 per 100 000 men to 4.84 per 100 000. Although the rates increased among both white and black males, the increases observed were different in each group.…”
Section: Incidencementioning
confidence: 99%
“…3 In Canadian and U.S. white populations, the incidence of nonseminoma has been increasing less rapidly than that of seminoma. 7,8 No adequate explanations for these trends have been identified, as the etiologies of these malignancies remain largely unknown.As investigations into secular trends of testis cancer have generally focused on populations of European ancestry, it is not clear whether rates in low-incidence populations also have increased over time. A study on international cancer trends between 1973-1987 by the International Agency for Research on Cancer (IARC) clearly demonstrated rising testis cancer rates in Japan and Puerto Rico but not in other low-incidence registries.…”
mentioning
confidence: 99%
“…Testicular germ cell tumour (TGCT) is the most common type of malignancy in young males aged 15 -35 years and the incidence is increasing steadily throughout the world (McGlynn et al, 2003). In the past 30 years, the incidence of TGCT has doubled, especially in young men with a mean age of 36 years at diagnosis (Power et al, 2001).…”
mentioning
confidence: 99%